2001
DOI: 10.1021/jm010080x
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Analogues of the Experimental Alzheimer Drug Phenserine:  Synthesis and Structure/Activity Relationships for Acetyl- and Butyrylcholinesterase Inhibitory Action

Abstract: With the goal of developing potential Alzheimer's pharmacotherapeutics, we have synthesized a series of novel analogues of the potent anticholinesterases phenserine (2) and physostigmine (1). These derivatives contain methyl (3, 4, 6), dimethyl (5, 7, 8, 10, 11) and trimethyl (14) substituents in each position of the phenyl group of the phenylcarbamoyl moieties, and with N-methyl and 6-methyl substituents (12, 13, 31, 33). We also quantified the inhibitory action of these compounds against human acetylcholines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
78
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 30 publications
(117 reference statements)
2
78
0
Order By: Relevance
“…The lack of a significant difference in k i between the enantiomers of the N-methyl,N-ethyl carbamate derivative of the AI series led us to conclude that the configuration of the chiral carbon in the rigid cyclopentyl moiety of aminoindan is not important for inhibition of rhAChE by the AI derivative, but chirality does influence inhibition by rivastigmine both of rhAChE (Bar-On et al, 2002) and hBChE, as shown previously by others (Yu et al, 2001;Luo et al, 2006).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The lack of a significant difference in k i between the enantiomers of the N-methyl,N-ethyl carbamate derivative of the AI series led us to conclude that the configuration of the chiral carbon in the rigid cyclopentyl moiety of aminoindan is not important for inhibition of rhAChE by the AI derivative, but chirality does influence inhibition by rivastigmine both of rhAChE (Bar-On et al, 2002) and hBChE, as shown previously by others (Yu et al, 2001;Luo et al, 2006).…”
Section: Discussionsupporting
confidence: 73%
“…Most published analyses of structure-activity relationships of carbamates designed as potential drugs for the treatment of AD are based on measurements of IC 50 (Yu et al, 2001;Sterling et al, 2002;Bolognesi et al, 2004;Luo et al, 2005Luo et al, , 2006Bartolucci et al, 2006). However, this parameter lacks information on the individual rate constants that govern the approach to, and the steady-state level of, enzyme activity and the rate of release of a leaving group designed to exert independent biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…Initial in vitro studies indicated the suitability of PS for transdermal application, as would be predicted from its physicochemical characteristics (Ozawa et al, 1988;Yu et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The additional demonstration that central BChE rather than AChE inhibition is the best correlate of cognitive improvement in AD clinical studies with the dual cholinesterase inhibitor rivastigmine ( Figure 2) further suggests that BChE represents an intriguing target to develop drugs for the treatment of neurodegenerative disease [19][20][21] . The derivatives of physostigmine ( Figure 2) are also potential drugs for the treatment of AD 22,23 . Since rivastigmine 24 , bambuterol 25 , and physostigmine are carbamates, inhibition mechanisms of both AChE and BChE by carbamates may play important roles for the treatment of AD [19][20][21][22][23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…The derivatives of physostigmine ( Figure 2) are also potential drugs for the treatment of AD 22,23 . Since rivastigmine 24 , bambuterol 25 , and physostigmine are carbamates, inhibition mechanisms of both AChE and BChE by carbamates may play important roles for the treatment of AD [19][20][21][22][23][24][25][26][27] . Carbaryl (1-naphthyl N-methylcarbamate, Sevin) (Figure 2), carbofuran (Furadan), propoxur (Baygon), and aldicarb (Temik) are carbamate pesticides that have activities against a broad range of insects and low mammalian toxicity 28 .…”
Section: Introductionmentioning
confidence: 99%